Evolution of Explosive Strength Data in Youth Volleyball Players Before and After Pandemic - Francesca D'Elia; Tiziana D'Isanto; Gaetano Altavilla; Gaetano Raiola (OVS LLC, 2021)
Study purpose. This study aims to verify if there are significant differences and which type of correlation is between anthropometric and jumping ability variables by testing a group (elite) of Italian volleyball players (under 16), just after a month of training, applying a specific protocol. Materials and methods. In all subjects, the following anthropometric and jumping ability parameters were assessed: height, weight, body mass index, height with a stretched arm (Reach1) and height with two extended arms (Reach2). The jumping ability was measured with the Squat jump (SJ) and Run-Up (RU) test. All data on anthropometric and jumping ability parameters were presented as mean and standard deviation (Mean ± SD). Results. The results of the jumping ability parameters (Squat Jump and Run-Up) showed significant differences between treatment initial-final: Run-Up with p = 0.000 and Squat Jump with p = 0.001; and these showed a higher correlation, especially the variables linked to the ability to jump, evident differences compared to the initial period of treatment. Conclusions. In high-level youth volleyball, the anthropometric and jumping ability profile is directly linked to the evaluation and continuous monitoring of physical qualities, and jumping ability becomes an important aspect for the control of performance.